Association between female infertility and stroke mortality: evidence from the PLCO cancer screening trial - Tang, Hui; Yang, Xueming; Li, Zhou; Zhang, Yuan; Chen, Huaxuan; Dai, Mingjun; Shao, Chuan (Frontiers in Endocrinology, 2024)
Objective: While infertility affects about 15% of women during their reproductive years, its long-term impact on stroke mortality after this period remains unclear. This study aims to investigate the association between infertility and stroke mortality in women using data from the Prostate, Lung, Colorectal, and Ovarian (PLCO) cancer screening trial. Methods: We analyzed data from 75,778 female participants aged 55-74 years with a median follow-up of 16.84 years. Cox proportional hazard models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for stroke mortality, adjusting for potential confounders. Results: Among participants, 14.53% reported infertility. During follow-up, 1,159 women died from stroke. Compared to women without infertility, those with infertility had a higher risk of stroke mortality (HR 1.21, 95% CI 1.04-1.41, p = 0.016). This association remained statistically significant after adjusting for age, race, education level, marital status, smoking status, body mass index, history of hypertension, history of heart attack, history of diabetes mellitus, birth control pill use, hormone replacement therapy, endometriosis, first menstrual period and pregnancy history (HR 1.20, 95% CI 1.02-1.42, p = 0.029).Sensitivity and subgroup analyses yielded consistent results. Conclusions: The findings of this study indicate that infertility is associated with an increased risk of stroke mortality in women. Further research is needed to confirm these findings and elucidate the underlying mechanisms.